A Ground Motion Record Selection Approach Based on Multiobjective Optimization. Issue 4 (21st April 2019) - Moschen, Lukas; Medina, Ricardo A.; Adam, Christoph
ABSTRACT: The evaluation of the seismic safety and reliability of buildings and building contents within a probabilistic framework often requires response history analyses using site-specific ground motion records. The ground motion selection method proposed in this paper addresses this issue by a stochastic search procedure in which record sets are selected such that first- and second-order statistics (median and dispersion) satisfy predefined ground motion spectrum targets over a wide period range. Once a ground motion record set is selected, it can be used for seismic assessment of a broad class of buildings within the target period range at the given location.